EFFECT OF INTEGRATED CROP MANAGEMENT PRACTICES ON YIELD AND ECONOMICS OF WATERMELON (Citrullus lanatus L.) IN KHAMMAM DISTRICT OF TELANGANA - V. CHAITANYA; J. HEMANTHA KUMAR; P. JAGAN MOHAN RAO; B. R. MADHUSHEKAR; Y.G. PRASAD (The Bioscan, 2021)
The present investigation was conducted in different villages under Krishi Vigyan Kendra, Wyra, Khammam operational areas during 2016-17 to 2018-19. Total 30 front line demonstrations were laid out on farmers’ fields in the district. The result of present study revealed that average highest yield 41.5 t/ha was noted in demonstration plot over control (28.5 t/ha) and 43.31 percent of average yield increase was recorded over control plot. Fruit cracking percentage was high in control plot (20.26%) over demonstration plot i.e 10.06 percent. The extension gap ranged from 12.5 t/ha to 13.5 t/ha and technology gap ranged between 5 to 11.5 t/ha respectively, with the technology index of 17 percent during the demonstration years. Besides this, the demonstrated plots gave higher gross returns, net returns with higher benefit cost ratio when compared to farmer’s practice. In present study efforts were also made to study the impact of FLD on horizontal spread which has increased by 105 %, if appropriate package and practices were followed. Further, the study was undertaken to do a formative and summative (outcome and impact) evaluation of the frontline demonstration on integrated crop management in watermelon.